Polymorphic crystalline structure and diversified crystalline morphology of poly(butylene adipate) blended with low‐molecular‐mass liquid crystals. Issue 2 (8th January 2020) - Xu, Wenqing; Zheng, Ying; Bao, Jianna; Li, Xing; Bao, Yongzhong; Shan, Guorong; Pan, Pengju
Abstract: Due to the multiple phase transition of liquid crystal, the semicrystalline polymer would exhibit the diversified crystalline structure and morphology in its mixture with liquid crystals. Herein, we choose polymorphic poly(butylene adipate) (PBA) as a model semicrystalline polymer, 4‐cyano‐4′‐n‐pentylbiphenyl (5CB) as a liquid crystalline diluter and studied the crystallization kinetics, polymorphic crystalline structure, crystalline structural transition, and crystalline morphology of PBA/5CB mixtures. The spherulitic growth rate and crystallization rate of PBA decrease after mixing with 5CB, attributing to the dilution effect of liquid crystals. Compared to neat PBA, the formation of thermodynamically stable α crystals is favored in the PBA/5CB blend at the same crystallization temperature ( T c ), ascribed to the depression of equilibrium melting temperature of PBA. The heating‐induced β‐to‐α transition of PBA crystals shifts to lower temperature in the PBA/5CB blend compared to the neat PBA. The crystalline morphology of PBA is strongly influenced by the incorporation of 5CB. The long period of PBA crystals enhances with the addition of a small amount of 5CB, due to the interlamellar segregation of 5CB in PBA crystals. The distribution of 5CB changes from the interlamellar to interspherulitic or interfibrillar regions of PBA crystals as the 5CB content increases in the PBA/5CB blend. Abstract : This study reports the polymorphic crystalline structure, phase transition, and diversified crystalline morphologies of polymorphic poly(butylene adipate) (PBA) blended with the small molecule liquid crystal, that is, 4‐cyano‐4′‐n‐pentylbiphenyl (5CB). Blending with 5CB facilitates the formation of α crystals and the heating‐induced β‐to‐α transition of PBA in the PBA/5CB blend. Distribution of 5CB changes from the interlamellar to interspherulitic or interfibrillar regions of PBA crystals as the 5CB content increases.